Aristotle and the Ọmọlúwàbí Ethos: Ethical Implications for Public Morality in Nigeria - Sunday Olaoluwa Dada (Yoruba Studies Review)
This essay explores the philosophical affinity between Aristotle’s concept of virtue as character habituation and the Yorùbá ethical and ontological understanding of ọmọlúwàbí as the foundation for re-examining the philosophical foundation of democratic governance in Nigeria. Based on the Aristotelian insistence that the good life is the end of politics, the essay argues for a rethinking of the concept of public morality as character-based political dynamics that enables politicians to think more about the social contract between the government and the governed, rather than an amoral understanding of politics that eschew morality and undermines the well-being of the citizens. The absence of public morality, the essay argues, has resulted in a neopatrimonial framework within which the political elite willfully circumvent constitutional rules and regulation in order to vitiate the public interest. The essay concludes by arguing for a rigorous public enlightenment as well as a reform of the educational curriculum through an injection of virtue ethics.